Penilaian Organisasi Perangkat Daerah (OPD) tentang Otoritas Veteriner dalam Kebijakan Penanggulangan Rabies di Provinsi Banten - Ismadi, Joko; Sumiarto, Bambang; Nugroho, Widagdo Sri; Purwanto, Erwan Agus (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Veterinary Authority (Otovet) is a government institution, formed in order to deal with decision making of anything related to animal health, by involving veterinarians and mobilizing all related professional lines. The purpose of this study was to describe the Regional Organizations’ (OPD) assessment of the implementation of Veterinary Authority (Otovet) in rabies management policies. Research material included 36 Regional organizations (OPD), 9 Technical services, supervising animal health (keswan) and veterinary public health (kesmavet), 9 Health services, 9 Regional development planning services, 9 Regional staffing services, Banten Province. The results comprised eight questions: 1). Are the organization bureaucratic? 2). Positions, roles, and authority of veterinarians? 3). Is the veterinary authority regarding rabies control already in line with the implementation? 4). Strategic policy 5). Cooperations OPD, 6). Regional Policy 7). Veterinarian openings, and 8). Enforcement and improvement of otovet institutions. The answers were: Technical services of animal health and veterinary public health: 0%, 33,33%, 77,78%, 100%, 33,33%, 44,44%, 77,78%, 100% answered yes; 100%, 66,67%, 22,22%, 0%, 66,67%, 55,56%, 22,22%, 0% answered no. Health services: 22,22%, 66,67%, 88,89%, 44,44%, 55,56%, 22,22%, 0% , 77,78% answered yes; 77,78%, 33,33%, 11,11%, 55,56%, 44,44%, 77,78%, 100%, 22,22% answered no. Regional development planning services, 33,33%, 88,89%, 66,67%, 11,11%, 33,33%, 33,33%, 33,33%, 100% answered yes; 66,67%, 11,11%, 33,33%, 88,89%, 66,67%, 66,67%, 66,67%, 0% answered no; Regional staffing services 88,89%, 77,78%, 55,56%, 0%, 11,11%, 11,11%, 100%, 66,67% answered yes; 11,11%, 22,22%, 44,44%, 100%, 88,89%, 88,89%, 0%, !00%, answered no. In conclusion, based on the quantitative data collected, the Regional Organizations’ (OPD) assessment of the implementation of Veterinary Authority (Otovet) in rabies management policies were as follows: 4 OPDs scored well and 5 OPDs scored poor. Health services: 4 OPDs scored well and 5 OPDs scored poor. Regional development planning services: 4 OPDs scored well and 5 OPDs scored poor. Regional staffing services: 1 scored well and 8 scored poor.